New Alkenylresorcinols with Cytotoxic and Antimicrobial Activities from the Leaves of Embelia schimperi - Togue, Tatiana Arlette M.; Ndontsa, Blanche Laure; Bitchagno, Gabin Thierry M.; Schüffler, Anja; Opatz, Till; Tane, Pierre; Tene, Mathieu (Planta Medica, 2020)
A phytochemical study of the methanol extract of the leaves of Embelia schimperi resulted in the isolation of three new alkenylresorcinols, 1 – 3, together with the known analogs 4 – 7. Their structures were established by a combination of spectroscopic techniques. Compounds 1 – 7 exhibited moderate cytotoxic activity against human cervical cancer cells HeLa-S3 and more pronounced antimicrobial properties towards bacteria and filamentous fungi. The present study falls into an ongoing research project on the characterization of bioactive phenolic lipids from plants of the family Primulaceae.
Keywords: Embelia schimperi; Primulaceae; structure elucidation; alkenylresorcinol; cytotoxicity; antimicrobial activity